The Effect of Katuk Leaves on Breast Milk Production in Postpartum Mothers at Wanayasa Health Center, Purwakarta Regency, Indonesia - Nurhayati Nurhayati (Archives of The Medicine and Case Reports, 2023)
The low coverage of exclusive breastfeeding is a challenge for midwives to be more active in promoting health about the importance of exclusive breastfeeding for baby growth. This low coverage of exclusive breastfeeding can have an impact on the quality of life of the nation's future generations and also on the national economy. One effort to increase the rate of secretion and production of breast milk is through giving katuk leaves. This study aimed to determine the effectiveness of katuk leaves on breast milk production in postpartum mothers. This study is an experimental research with a pre-post-test approach with control group design. A total of 30 research subjects were included in this study, where the research subjects were given an intervention with 200 mg katuk leaf extract given 1x200 mg for 7 days, where the assessment of breast milk production was carried out before and after the intervention. This study shows that the intervention of giving katuk leaf extract is effective in increasing breast milk production. There was an increase in breast milk production after giving katuk leaf extract and it was stated to be statistically different, p<0.05. In conclusion, there is an effect of giving katuk leaves on breast milk production for postpartum mothers at the Wanayasa Health Center, Purwakarta Regency, Indonesia.